Market Conditions and Fund Flows: Evidence from Hedge Funds (International Journal of Banking and Finance, 2013)
This paper investigates whether market conditions affect fund investor behaviour in the hedge fund industry, especially the volatility in the up and down markets. Using a sample of 5,254 individual hedge funds from January 1994 to December 2009, we find that hedge fund investors tend to invest less during up and down-volatile markets. They also adopt different investment strategies in these two market conditions. When market is calm and relatively predictable, there is almost no difference in their behaviors between up and down markets. We also find that smart money effect exists over both 3- and 12-month periods under all market conditions except volatile markets. A further investigation suggests that the observed smart money effect is largely driven by hedge fund performance persistence, which is present and significant is quiet markets only. The findings are relevant to portfolio theories concerning investor recognition of upside and downside volatilities.